Bio-efficacy of agro-industrial wastes treated with neem leaf extract on the growth and yield of Pleurotus sajor-caju - Toppo, Swati Rose; Baghel, Sunil; Baghel, Sunil (Mushroom Research, 2020)
This research work was carried out to use locally available agro-industrial wastes such as wheat straw and maize stover as substrates for cultivation of Pleurotus sajor-caju and to check the efficacy of neem leaf extract as biocontrol agent for oyster Mushroom cultivation. In the present work for cultivation Pleurotus sajorcaju, spawn run was completed after 19-25 days of inoculation and pinheads were formed 2-3 days after the spawn running that is 22- 27 days after inoculation. The fruiting bodies appeared 5-7 day after pinhead formation and took 27-34 days after spawning. The total cropping duration of 82 days was recorded for Pleurotus sajor-caju from treatment T5 (wheat straw + maize stover + NE as substrate). Maximum average yield 4.4 kg/kg dry weight of substrate was obtained from the treatment T5 (wheat straw+maize stover+ NE as substrate) in which Neem leaf extract treatments showed increased yield with highest biological efficiency of 89.6%. Neem leaf extract treatments showed decrease in incidence of mycopathogenic infection in mushroom beds. The present work focuses on the exploration of locally available agro-industrial wastes for mushroom bed preparation and introduction of Neem leaf extract treatment during the course of oyster mushroom cultivation as it exerts antimicrobial activity that inhibited various fungal pathogens in mushroom compost.